2018
DOI: 10.1007/s00167-018-5209-7
|View full text |Cite
|
Sign up to set email alerts
|

The concomitant lateral meniscus injury increased the pivot shift in the anterior cruciate ligament-injured knee

Abstract: Purpose Concomitant meniscus injuries in the anterior cruciate ligament (ACL) injuries have been suggested to exacerbate rotational laxity. However, the effect is supposed to be so small, if any, that some quantitative pivot-shift measurement is needed. The purpose of this prospective study was to determine the effect of meniscus tear on rotational laxity in ACL-deficient knees by an quantitative measurement. We hypothesized that a concomitant meniscus tear, especially a lateral one, would induce greater pivot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…Previous work by the authors of this study and others have demonstrated lateral meniscus pathology to be a key factor contributing to a more explosive pivot-shift as measured by various quantitative assessments. 2,3 Further, our group has demonstrated more chronic ACL tears to be associated with a greater risk of a high-grade pivot-shift by manual assessment, 4 and this study confirms that finding with a more quantitative measurement methodology.…”
Section: See Related Article On Page 1398supporting
confidence: 77%
“…Previous work by the authors of this study and others have demonstrated lateral meniscus pathology to be a key factor contributing to a more explosive pivot-shift as measured by various quantitative assessments. 2,3 Further, our group has demonstrated more chronic ACL tears to be associated with a greater risk of a high-grade pivot-shift by manual assessment, 4 and this study confirms that finding with a more quantitative measurement methodology.…”
Section: See Related Article On Page 1398supporting
confidence: 77%
“…25,29,32 Whereas anterior tibial translation has been shown to be significantly higher in ACL injuries with medial or lateral meniscal tears (3.7 vs 2.7 mm, respectively), 27 tibial acceleration was influenced by only lateral meniscal tears (2.1 ± 1.1 vs 1.2 ± 0.7 m/s 2 , respectively). 12 The present study demonstrated that anatomic ACLR with appropriate meniscal repair resulted in excellent restoration of rotatory laxity as measured by the pivot-shift test, as well as acceptable PROs, at 24-month follow-up.…”
Section: Discussionsupporting
confidence: 56%
“…25 Individualized treatment for patients with ACL injuries is important, and the QPS may help direct attention to additional soft tissue injuries, ensuring complete restoration of rotatory knee stability, as shown in this study. 12,25,27 Moreover, in 1 case, the pivot-shift test was helpful in confirming intraoperative knee stability. In this patient, the QPS was equal at time zero postoperatively compared to preoperative measurements, which led to an investigation into femoral fixation with fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantage of ETS is that it is cumbersome and unable to be easily used outside of a laboratory or clinical-based setting. Recently, however, a more clinically friendly device that measures knee kinematics using only two electromagnetic sensors (on the thigh and shank) has been reported [23,24]. This compact ETS also enables quantitative evaluation of the pivot shift test pre-and post-anterior cruciate ligament (ACL) reconstruction.…”
Section: Electromagnetic Sensorsmentioning
confidence: 99%